1-Butyl-3-methylimidazolium Salts as New Catalysts to Produce Epoxy-anhydride Polymers with Improved Properties. (13th May 2014) - Fedoseev, Mikhail S.; Gruzdev, Matvey S.; Derzhavinskaya, Lubov F.
Abstract : We report the curing process of epoxy oligomers by using isomethyltetrahydrophthalic anhydride catalyzed with 1-butyl-3-methylimidazolium salts. Catalytic action has been ascertained to be dependent on the nature of anion. Salts with ( B r - ) and ( P O 4 - ) anions appeared to be most active. Formation of salt adducts with epoxy resin and anhydride is shown. Polymers having higher values of strength and glass transition temperature—as compared with similar epoxy systems cured in the presence of tertiary amines as catalysts—are prepared.